Sex Determination using Condylar Height in south Indian population - A Retrospective Study - Anuja, P; Doggalli, N; Patil, K; Rudraswamy, S; Johnson , A; Syed , WP (Journal of Indian Academy of Forensic Medicine, 2024)
Mandibular parameters evaluation has been used to determine sex in forensics and for treatment planning in dentistry. The present study aims to determine condylar height in a group of 20 to 70 years old males and females using panoramic radiographs for sex determination. This study was performed to measure the height of the condyle indicating that females and males showed significant differences for condylar height by 5.81 mm. The results of the present study indicate that condylar ramus height can be used effectively for sex determination.